Speech delivered by Dr. Salvador Allende, President of the Republic of Chile before The General Assembly of The United Nations, December 4, 1972. (Embassy of Chile, 1972)
Reproduce el discurso pronunciado por el Presidente de la República de Chile, Dr. Salvador Allende, con motivo de la Asamblea General de las Naciones Unidas del 4 de diciembre de 1972.